2021
DOI: 10.1136/bmjopen-2020-042125
|View full text |Cite
|
Sign up to set email alerts
|

Are adverse childhood experiences associated with late-life cognitive performance across racial/ethnic groups: results from the Kaiser Healthy Aging and Diverse Life Experiences study baseline

Abstract: ObjectivesEvidence on adverse childhood experiences (ACEs) and late-life cognitive outcomes is inconsistent, with little research among diverse racial/ethnic groups. We investigated whether ACE exposures were associated with worse late-life cognition for all racial/ethnic groups and at different ages of exposure.DesignCovariate-adjusted mixed-effects linear regression models estimated associations of: (1) total number of ACEs experienced, (2) earliest age when ACE occurred and (3) type of ACE with overall cogn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 24 publications
(22 reference statements)
5
27
0
Order By: Relevance
“…Cross-Sectional Analysis. To simplify interpretation and increase power, we assessed whether it was appropriate to estimate a single effect of each exposure (social integration and daily interaction with a confidant) on all three cognitive domains by testing whether the race-specific association of each exposure with cognition differed depending on the cognitive domain assessed, following Gold et al 27 To do this, we fit a linear mixed-effects model predicting Y ij, where i indexes the individual and j indexes the cognitive domain. This approach treats each of the three cognitive domain assessments as repeatedly measured outcomes for each individual, adjusting for an indicator of which domain was being measured (executive function was the reference group).…”
Section: Discussionmentioning
confidence: 99%
“…Cross-Sectional Analysis. To simplify interpretation and increase power, we assessed whether it was appropriate to estimate a single effect of each exposure (social integration and daily interaction with a confidant) on all three cognitive domains by testing whether the race-specific association of each exposure with cognition differed depending on the cognitive domain assessed, following Gold et al 27 To do this, we fit a linear mixed-effects model predicting Y ij, where i indexes the individual and j indexes the cognitive domain. This approach treats each of the three cognitive domain assessments as repeatedly measured outcomes for each individual, adjusting for an indicator of which domain was being measured (executive function was the reference group).…”
Section: Discussionmentioning
confidence: 99%
“…For example, ACEs have been linked to cognitive decline and impairments during adolescence (< 18 years of age) as well as older age (> 60 years; Blakemore, 2019 ; Halpin et al, 2021 ; Korten et al, 2014 ; Murman, 2015 ; Verhaeghen & Salthouse, 1997 ). However, the association between adverse childhood experiences, increasing age, and cognitive deficits is not well-understood (Gold et al, 2021 ; Ritchie et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the relationship between ACEs and cognition was inconsistent between studies. For example, some studies showed that the number of ACEs was not adversely related to later-life cognitive function after adjusting for the covariates,14 15 whereas other studies reported that ACEs were related to worse cognitive function and faster cognitive decline 16 17. Other studies indicated that both child maltreatment and childhood stress increased the all-cause risk of dementia in elderly and middle-aged people 18 19.…”
Section: Introductionmentioning
confidence: 99%